The Relationship Between Self-Regulated Learning and Academic Adjustment Among Students at MAS Darul Ulum Banda Aceh - Arifa, Fitria; Jannah, Miftahul (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The demanding academic workload and intensive daily activities require students to possess good academic adjustment skills. One way to enhance academic adjustment is by developing the ability of self-regulated learning. The purpose of this study was to determine the relationship between self-regulated learning and academic adjustment among students at MAS Darul Ulum Banda Aceh. This research employed a quantitative approach using a correlational method. The subjects in this study were 95 tenth-grade students of MAS Darul Ulum Banda Aceh, with a total population of 132 students. Sampling was conducted using the simple random sampling technique. Data analysis was carried out using the Pearson Product-Moment correlation test. The results showed a correlation coefficient of r = 0.596 with a significance value of p = 0.000. Therefore, it can be concluded that the research hypothesis is accepted, indicating a significant relationship between the two variables. This relationship suggests that the higher the level of self-regulated learning, the higher the level of academic adjustment. Conversely, the lower the self-regulated learning, the lower the academic adjustment.